2022
DOI: 10.1155/2022/6301902
|View full text |Cite
|
Sign up to set email alerts
|

Bidding Strategy of a Wind-Thermal GENCO considering Piecewise Linear AC Power Flow and Correlated Uncertainties

Abstract: In deregulated electricity markets, generation companies (GENCO) try to maximize their economic benefits considering the electricity demand, transmission network condition, and other participants’ behaviors. The increasing penetration of renewable sources such as wind power generation with intermittent nature poses several challenges to the participation of GENCOs in the electricity market. Thus, this paper presents a stochastic bilevel optimization model to determine the coordinated bidding strategy of a wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Of course, the basic requirement of this method is the convexity of the lower-level problem; however, this problem is non-convex due to the use of power flow equations [20,21]. Thus, to compensate for this challenge, a linear approximation model is first developed for the lower-level problem constraints [29][30][31]. Then a mixed-integer quadratically constrained program (MIQCP) model with quadratic objective function and linear constraints is obtained for the single-level problem.…”
Section: Contributionsmentioning
confidence: 99%
“…Of course, the basic requirement of this method is the convexity of the lower-level problem; however, this problem is non-convex due to the use of power flow equations [20,21]. Thus, to compensate for this challenge, a linear approximation model is first developed for the lower-level problem constraints [29][30][31]. Then a mixed-integer quadratically constrained program (MIQCP) model with quadratic objective function and linear constraints is obtained for the single-level problem.…”
Section: Contributionsmentioning
confidence: 99%
“…Te authors of reference [15] suggested a two-tier optimization model to defne the sales approach in the previous day's market considering comprehensive technologies of renewable wind energy. Te uncertainty of wind and load sources is modeled by the Monte Carlo scenario generation method considering their interdependence and the Copula method.…”
Section: Introductionmentioning
confidence: 99%
“…Te proposed model also provided a linearized model of IC load distribution to reduce the complexity of the problem. Daealhaq et al [15] proposed a top-of-the-line DC-DC solid-state transformer for two-way parking of photovoltaics/EV batteries with network vehicle service (V2G-PVBP). By considering the advantages of energy storing capacity of EVs, V2G-PVBP showed efciency in both satisfying the usual needs of electric vehicle owners and preparing load handling and load adjustment performance to the MG. Qin et al [16] introduced the optimal performance of a fuzzy controller to obtain balancing between energy consumption and energy generation in an independent microgrid (S-MG) in the presence of EVs.…”
Section: Introductionmentioning
confidence: 99%